Trust, trustworthiness and selection into the financial industry - Andrej Gill; Matthias Heinz; Heiner Schumacher (Goethe University Frankfurt, Center for Financial Studies (CFS), 2014)
We examine trust and trustworthiness of individuals with varying professional preferences and experiences. Our subjects study business and economics in Frankfurt, the financial center of Germany and continental Europe. In the trust game, subjects with a high interest in working in the financial industry return 25 percent less than subjects with a low interest. We find no evidence that the extent of professional experience in the financial industry has a negative impact on trustworthiness. We also do not find any evidence that the financial industry screens out less trustworthy individuals in the hiring process. In a prediction game that is strategically equivalent to the trust game, the amount sent by first-movers was significantly smaller when the second-mover indicated a high interest in working in finance. These results suggest that the financial industry attracts less trustworthy individuals, which may contribute to the current lack of trust in its employees.
Keywords: C9; G2; M5; 330; Trust; Trustworthiness; Selection; Financial Industry